Illuminating Progress: Charting an Energy-Driven Future for the Islamic World - Huswatun Miswar, Syarifah (UI Scholars Hub, 2024)
This paper examines the development of the energy sector in the Islamic world, focusing on the challenges and opportunities facing Organization of Islamic Cooperation (OIC) countries in the transition to sustainable energy. Despite being rich in natural resources, many Islamic countries are still dependent on fossil fuels and face constraints in universal energy access. This study analyzes the current energy landscape in OIC countries, identifies key barriers to energy development, and emphasizes the need for a new roadmap that integrates knowledge and development. The research also investigates the potential role of Islamic finance in funding sustainable energy projects, with a particular focus on innovations such as green sukuk. The global trend towards renewable energy and sustainable development is discussed in the context of the UN Sustainable Development Goals. The study finds that despite facing significant challenges, the Islamic world has a great opportunity to take the lead in the global energy transition by utilizing natural resources, innovative financial instruments, and a commitment to sustainable development. In conclusion, this journal highlights the importance of international collaboration, knowledge transfer, and sustainable investment in realizing a cleaner and more sustainable energy future for the Islamic world and the global community.